First report of Blastanosphaira kokkoda Javaux and Knoll 2017 from the Ediacaran of the Araras Group, Brazil (Western Gondwana): biostratigraphic and paleoenvironmental implications - Diego R. Rodrigues Cruz; Silane A. Ferreira da Silva-Caminha; Evelyn Aparecida Mecenero Sanchez; Rogério Roque Rubert; Gabriel Fernandes Coelho; Tainah Alves de Matos; Andressa Luiza Pereira de Camargo; Vinicius Santos do Valle; Juliana Okubo (Journal of South American Earth Sciences, 2026)

High-resolution study of pollutant mobility in an acid mine drainage-impacted estuary under changing tidal and river contributions - Laura Sánchez-López; Jonatan Romero-Matos; Carlos R. Cánovas; Rémi Freydier; Rafael Pérez-López (Journal of Hydrology, 2026)

Rainfall-driven, high-resolution assessment of water acidification in a planned reservoir within an unreclaimed historical mining basin - Jonatan Romero-Matos; Laura Sánchez-López; Rafael León; Francisco Macías; Carlos R. Cánovas; Manuel Olías; José Miguel Nieto (Environmental Pollution, 2026)

The genus Pouteria: a review of advances in phytochemical elucidation and its pharmacological properties - Rafael C. Matos; Ana Flavia A. Bitencourt; Vanessa R. Prado; Alexsandro D. M. Oliveira; Renes R. Machado; Marina Scopel (Phytochemistry Reviews, 2026)
The genus Pouteria (family Sapotaceae) is traditionally used for gastrointestinal, inflammatory, and microbial issues, and has great nutritional applications because of the variety of fruits it contains. Despite its versatile applications, comprehensive research on Pouteria remains outdated, necessitating an integrative review of recent studies exploring its phytochemical evidence and biological activities. An unrestricted search in various databases (Jan/2009 to Aug/2022) focused on the genus “ Pouteria ”. Despite this genus having 325 recognized species, few studies have evaluated their bioactive potential, including antioxidant, anticancer, hypoglycemic, antimicrobial, anti-inflammatory, and antinociceptive, as well as their potential for treatment of Alzheimer disease. Regarding phytochemical evaluation, among the few substances isolated were a high number of terpenoids, flavonoids, phenolics, saponins, and others. In addition, owing to the high potential for fruit utilization, several primary metabolites were identified, which presented qualitative and quantitative diversity among species with the interests of the pharmaceutical industry. Therefore, this review provides information about phytochemical and pharmacological properties of the species of Pouteria . Given the shallow and incomplete results for several species, there is a demonstrated need for new studies encompassing all plant parts of Pouteria species, contributing to a more comprehensive understanding of their medicinal potential.

Native Trichoderma spp. as biocontrol agents against common beans anthracnose - S. C. Izidoro-Morimitsu; A. Knob; C. K. Matos; C. M. D. R. Faria; J. Kawakami (Journal of Plant Diseases and Protection, 2026)

Identification of gene conversion events in horse IGHV suggests preferential hotspots for diversification - Juliana Edelvacy Lima Pinto; João Henrique Brandão Gervásio; Joseph Chi-fung Ng; Adriano Gomes-Silva; Herbert L. de Matos Guedes; Luiz Cunha; Leda R. Castilho; Jerson Lima da Silva; Glória Regina Franco; Carlena Navas; Liza Figueiredo Felicori (Immunogenetics, 2026)
The humoral immune response relies on a diverse antibody repertoire, which is expanded through processes such as somatic hypermutation, class-switch recombination and gene conversion. These processes are primarily mediated by activation-induced cytidine deaminase (AID). Gene conversion generates diversity in immunoglobulin heavy and light chains (IGHVs) in species such as chickens and rabbits, though it has not been widely studied. Since 80% of the equine IGHV repertoire originates from only three functional gene segments, we examined gene conversion events in horses to assess their role in antibody diversification. Using a modified version of BrepConvert, which optimized analysis time, we identified gene conversion events in 6.9% of immunoglobulin sequences. The results showed a local preference, with most events occurring at the beginning of framework region 1 (FR1) and within complementarity-determining region 2 (CDR2). Pseudogenes IGHV4-35, IGHV4-53, and IGHV4-38 were utilized most frequently, while functional genes IGHV4-21, IGHV4-22, and IGHV4-29 exhibited the highest event frequencies. Interestingly, while most mismatched regions were only three nucleotides long, 91% of these events are flanked by specific sequences (six nucleotides at the 5′ end and one nucleotide at the 3′ end). Furthermore, functional pseudogene pairs often share identical leader regions of 5–26 nucleotides, suggesting expanded events. We also identified a potential association between these events and local non-B DNA conformations, as well as with the zinc finger protein ZNF691, which supports the involvement of DNA-binding factors. Together, these findings demonstrate that gene conversion significantly contributes to equine antibody diversity by targeting specific IGHV regions.

Ready to eat, ready to risk? A retrospective evaluation of microbiological contamination and surveillance gaps in self-service meals in Bahia, Brazil - Joselene C.N. Nascimento; Danilo M. Vilas-Boas; Clícia C. Leite; Victor O. Martinez; Juliana R. Matos; Mariana N. Roselino; Cleber A. Schmidt; Wilson J.F. Lemos Junior; Anderson S. Sant’Ana; Alaíse G. Guimarães (Food Control, 2026)

Melatonin Alleviates Aluminum Toxicity in Pfaffia glomerata by Modulating Tolerance Mechanisms - Michelle M. V. Almeida; Juliane M. Henschel; Tatiane D. Silva; Luiza E. G. Monteiro; Mateus S. Rodrigues; Tadeu R. Oliveira; Auxiliadora O. Martins; Sérgio H. S. Felipe; Evandro A. Fortini; Elyabe M. Matos; Lyderson F. Viccini; Diego S. Batista; et al. (Journal of Plant Growth Regulation, 2026)
Aluminum (Al) toxicity is the main factor limiting agricultural production in acidic soils around the world. In this scenario, melatonin (MET) has emerged as a promising approach to alleviate Al toxicity. Thus, we investigated morphophysiological responses of Pfaffia glomerata (Spreng.) Pedersen, a medicinal plant, to Al toxicity and MET application. Plants were grown in vitro for 40 days in MS medium (control) supplemented with Al, MET, and Al + MET. Aluminum had genotoxic effects, inducing DNA damages and endoreduplication, which resulted in growth arrest, mainly in roots. Al also decreased the photosynthetic rate and the contents of pigments, carbohydrates, amino acids, and proteins. On the other hand, all these effects were improved in plants supplemented with MET. This is supported by the up-accumulation of proteins involved in organic acids exudation (AHA2), photosynthesis (transketolase, rubisco activase, and photosystem I P700 apoprotein A2), amino acid biosynthesis (chorismate synthase 1 and aspartokinase/homoserine dehydrogenase), and cell expansion and differentiation (rough sheath 2, beta tubulin b6, and tubulin beta chain-like). Moreover, MET enhanced CAT, SOD, and GABA, reinforcing its antioxidant role and reducing DNA damage and endoreduplication, which preserved QC identity and root elongation. Al toxicity impaired growth and carbon–nitrogen metabolism, whereas MET mitigated these effects by boosting photosynthesis, antioxidant defenses, and Al sequestration, decreasing Al adherence to roots. Thus, MET serves as a protective molecule against Al toxicity in P. glomerata .

Chemical investigation, dereplication studies by UHPLC-ESI-HRMSMS/molecular networking, and antiproliferative activity of Symphyopappus cuneatus (Asteraceae) - Márcia R. P. Cabral; Carla Porto; Drielli R. Areas; Maria G. Matos; Debora C. Baldoqui; Marta R. B. Carmo; Mary A. Foglio; Mariana Cecchetto; Ana Lucia T. G. Ruiz; Maria H. Sarragiotto (Natural Product Research, 2026)

Staphylococcus aureus in food safety: antimicrobial resistance, detection technologies, and future perspectives - Joselene C. Nunes Nascimento; Verônica O. Alvarenga; Bruno N. Paulino; Adriana B. de Cerqueira e Silva; Juliana R. Matos; Iuri L. dos Santos Rosário; Ivo Henrique P. Andrade; José Givanildo Silva; Marion Costa (Critical Reviews in Food Science and Nutrition, 2026)

Characterization and modeling approach for planning restoration strategies in a complex basin affected by acid mine drainage - Jonatan Romero-Matos; Laura Sánchez-López; Rafael León; Robert L. Runkel; D. Kirk Nordstrom; Carlos R. Cánovas; Francisco Macías; José Miguel Nieto (Journal of Environmental Management, 2026)

Geochemistry of the volcano-sedimentary complex of the Algarve Basin (Silves-Ayamonte, SW Iberia) - A. Díez-Montes; R. Solá; J. J. Huerta; S. Machado; R. Dias; J. X. Matos; M. López (Journal of Iberian Geology, 2025)
The Volcano-Sedimentary Complex of the Algarve basin (south of the Iberian Peninsula) belongs to the Large Igneous Province of the Central Atlantic Magmatic Province (CAMP), which developed c.200 Ma following the start of the breakup of Pangaea, and preceding the opening of the Atlantic Ocean. This volcanic complex was emplaced in a short period of time in the Lower Jurassic (Hettangian-Sinemurian). It includes subaerial lava flows, pyroclastic deposits and peperites, and contemporaneous sedimentation. We present new field evidence and geochemical data of mafic rock suites within a > 150 km long transect across the volcanic belt. The rocks have a subalkaline geochemical affinity and low TiO 2 contents. They are moderately evolved (Mg# 53–76) and have quartz-hypersthene-normative associations, classifying as low-Ti tholeiites (TiO 2 = 1.2–1.5 wt%). They have slight yet variable enrichment in light ion lithophile and light rare erath elements [(La/Yb) N = 2.55–3.40] and a negative Ta-Nb anomalies. The mafic rocks have enriched MORB compositions, compatible with low-Ti tholeiitic CAMP suites. A trait of CAMP basaltic flows is their compositional homogeneity. Distinct volcanic rocks are only described in the Algarve basin, and have relatively lower SiO 2 and high CaO contents than typical CAMP rocks. Our data suggest that the subset of volcanic rocks with lower SiO 2 and high CaO are linked to contamination-assimilation of ascending magmas with carbonate-evaporite material from Silves marl-carbonated-evaporitic complex, immediately underlying the CAMP sequences.

Bovine and ovine deltapapillomavirus coinfection associated with equine sarcoid - E. L. Pereira; G. R. Pereira; M. L. de Osório; J. L. A. Terra; J. B. Gayger; J. S. Gularte; M. Demoliner; V. M. A. G. Pereira; M. Filippi; Q. S. de Matos; A. Tessman; C. W. Canal; et al. (Brazilian Journal of Microbiology, 2025)

Genetic correlations between carcass traits measured by ultrasonography and semen quality traits in Nellore cattle incorporating genomic information - Camila S. Mussi; Gabriel C. Medeiros; Rafael Espigolan; Fernando Baldi; Marcio R. Silva; José D. Guimarães; Elisangela C. Matos; Joanir P. Eler; Tamires Miranda Neto; José Bento S. Ferraz; Luiz F. Brito (Livestock Science, 2025)

Evaluation of different small-scale constructed wetlands cultivated with ultrashort hydraulic retention time and reduced operational control - R. A. Crippa; M. S. Ázara; M. P. Matos; A. T. Matos; R. Fia; L. C. Lima; A. L. P. Valácio; T. R. Silva (International Journal of Environmental Science and Technology, 2025)

Tides of rebirth: A stratigraphic perspective on the Lazarus effect in freshwater bivalves in the Aptian-Albian Romualdo Formation, Araripe Basin, Brazil - Marcello G. Simões; Vitor B. Guerrini; Victor R. Silva; Filipe G. Varejão; Suzana A. Matos; Mariza G. Rodrigues; Lucas V. Warren; Mario L. Assine; Franz T. Fürsich (Cretaceous Research, 2025)

Addressing Critical Fungal Pathogens Under a One Health Perspective: Key Insights from the Portuguese Association of Medical Mycology - R. Sabino; F. Antunes; R. Araujo; A. R. Bezerra; J. Brandão; C. Carneiro; A. Carvalho; D. Carvalho; I. C. Conceição; F. Cota Medeiros; C. Cruz; E. Duarte; et al. (Mycopathologia, 2025)
Fungal infections have emerged as a significant public health concern, especially with the increasing incidence of severe mycoses caused by pathogens such as Aspergillus fumigatus , Candida auris , Candida albicans , and Cryptococcus neoformans . These fungi, listed as critical priorities by the World Health Organization, pose a heightened risk due to rising antifungal resistance and their severe impact on immunocompromised individuals. This article, coordinated by the Portuguese Association of Medical Mycology, highlights the importance of adopting a One Health perspective to address fungal threats comprehensively. Drawing on interdisciplinary collaboration, the association aims to foster greater awareness, improve diagnostic capabilities, and stimulate research and public health policies in Portugal but also at global level. The paper outlines key strategies for surveillance, prevention, and innovation in fungal diagnostics and therapeutics. Moreover, it emphasizes the urgent need for national coordination and international cooperation in managing fungal infections, advocating for integrative approaches that link human, animal, and environmental health. By presenting a consolidated overview of current challenges and future priorities, this work seeks to enhance preparedness and response mechanisms in the face of escalating fungal threats.

The role of nest-site interference competition with Cape Verde Shearwater in explaining breeding success of Red-billed Tropicbird on Raso Islet, Cape Verde archipelago - Jaime A. Ramos; Catelene Monteiro; Isabel Rodrigues; Diana M. Matos; Vitor H. Paiva; Filipe R. Ceia; Jorge M. Pereira; Kenny Delgado; Stefan Antunes (Journal of Ornithology, 2025)

Unveiling the Secret: Effect of Grape Stems as Soil Amendments in Earthworm Tail Regeneration and Reproductive Success - Tiago Azevedo; Marta Roboredo; Ana I. R. N. A. Barros; Irene Gouvinhas; Lara Anjos; Rafael Araújo; João R. Sousa; Isabel Gaivão; Maria de Lurdes Pinto; Manuela Matos; Francisco Peixoto; Maria Manuel Oliveira; et al. (Journal of Soil Science and Plant Nutrition, 2025)
The increasing reliance on agricultural machinery to improve agronomic output and meet food demands disrupts soil structure and poses risks to soil biota, including mechanical injuries to earthworms. This study assesses the potential of grape stems as a soil amendment to promote earthworm regeneration and investigate their impact on reproduction and oxidative stress. Four experimental conditions were established: a control group (E0) with OECD reference soil and three groups where ground grape stems replaced 5% (E5), 10% (E10) and 25% (E25) of peat. Earthworms ( n = 10/replicate) were amputated 30 segments past the clitellum. Destructive sampling occurred at 15, 30, and 45 days post-amputation. Regenerated segments were measured/counted, while adjacent tissue and blastema were analysed for oxidative stress markers (catalase (CAT), glutathione S-transferase (GST), peroxidase (POD), superoxide dismutase (SOD) activities). Reproductive output was assessed 60 days post-amputation. Regeneration outcomes revealed a nuanced relationship with grape stem amendments, demonstrating non-lethal effects and enhanced reproduction at certain concentrations. However, higher grape stem percentages (E25) revealed a slight delay in regeneration. Grape stem exposure induced changes in antioxidant enzyme activities, particularly in detoxification mechanisms mediated by GST and POD, with distinct activity levels observed in blastema and adjacent tissues. Grape stems as soil amendments demonstrate potential benefits for earthworm health, including improved reproduction and modulated oxidative stress responses. However, optimal application rates are crucial to avoid adverse effects on regeneration. These findings highlight the dual role of soil amendments in nutrient provision and promoting the well-being of soil organisms. Graphical Abstract

Microclimate simulation and lichen-based validation analyzing street trees' impact on atmospheric pollutant dispersion at the urban canyon scale - Carolina Girotti; Paula Sofia Antunes Matos; Alessandra R. Prata Shimomura; Fernando Akira Kurokawa; Ezequiel Correia; António Lopes (Urban Climate, 2025)

Observations of Sargassum carbon influx and biogeochemical impact in La Parguera Marine Reserve - Priscilla N. Molina-Cora; Julio M. Morell; Loraine Martell-Bonet; Luis R. Rodriguez-Matos; Julián E. Morell; Maribel Vélez-Rivera (Frontiers in Marine Science, 2025)
The massive influx of pelagic Sargassum spp. species, also known as Sargassum inundation events (SIEs), first arrived at the Caribbean’s coastal waters in 2011. These events have been linked to hypoxia, among other ecological disturbances. Here, we report data from 2022 on (1) an assessment of the relative magnitude of particulate organic carbon (POC) load arising from SIEs into the La Parguera Marine Reserve (LPMR) basin off the southwest coast of Puerto Rico and (2) the biogeochemical impact of SIE in a nearshore mangrove key within the reserve, Monsio Jose Key Bay (MJKB). Our analysis yields that the carbon influx increased by 20% in the LPMR basin and by 103% in MJKB. Weekly observations of Sargassum input, along with the collection and analysis of water samples in MJKB, evidenced a cause-effect relation between Sargassum carbon loading and frequency of hypoxic (DO < 2 mg·L -1 ) and critically acidic conditions (Aragonite saturation, Ω < 2.0). During the 2022 Sargassum season, hypoxic conditions were detected in 43% of samples collected in MJKB. Considering the modulation of biogeochemical parameters by changes in tide height (Δh) and wind speed (m·s -1 ), stepwise multiple regression analyses (RDA-AIC model selection) showed that significant parameters influencing DO, pH, and Ω include the Sargassum carbon influx and Δh ( p < 0.05). These findings strongly support the hypothesis that the additional input of POC influx enhances microbial mineralization rates responsible for depressed oxygen concentrations and acidic conditions, which could be detrimental to coastal ecosystems. This is particularly concerning in areas prone to SIEs where geomorphological features facilitate the entrainment of floating materials. Proper management requires the identification of vulnerable sites and Sargassum removal. Ongoing efforts towards that goal are underway for LPMR.

Seagrass biochemical response to transplantation into contaminated sediments: A mesocosm experiment - Vitor H. Oliveira; B.A. Fonte; A.I. Sousa; B. Marques; D. Matos; B. Henriques; M.E. Pereira; C.B. Lopes; R. Calado; A.I. Lillebø; E. Figueira; J.P. Coelho (Environmental Research, 2025)

Corymbia citriodora hydrodistillation optimization: A biorefinery approach for extracting high value biocompounds - Aline K. Soares; Fabrício A. Hansel; Mauricio de Matos; Gabriel G. de Lima; Dayanne R.M. Andrade; Rosinaldo R. Aparício; Ivana A. Dias; Pedro H.G. de Cademartori; Washington L.E. Magalhães (Chemical Engineering Journal, 2025)

Insights into the thermal stability properties of two hardwoods from the Amazon rainforest - L. de Souza-Cavalcante; F. Guerrero; J. Anglada-Rivera; Y. Leyet; F. M. A. da Silva; G. Q. Ramos; R. Matos; H. D. da Fonseca Filho (Journal of the Indian Academy of Wood Science, 2025)

Do (xeno)estrogens pose a risk to earthworms? Soy isoflavones and estradiol impact gonad structure and induce oxidative stress in Eisenia fetida - Tiago Azevedo; Rita Silva-Reis; Beatriz Medeiros-Fonseca; Mariana Gonçalves; Gabriel Mendes; Marta Roboredo; Maria J. Rocha; Francisco Peixoto; Maria de Lurdes Pinto; Manuela Matos; João R. Sousa; Paula A. Oliveira; et al. (Chemosphere, 2025)

The importance of tropical tree-ring chronologies for global change research - Peter Groenendijk; Flurin Babst; Valerie Trouet; Ze-Xin Fan; Daniela Granato-Souza; Giuliano Maselli Locosselli; Mulugeta Mokria; Shankar Panthi; Nathsuda Pumijumnong; Abrham Abiyu; Rodolfo Acuña-Soto; Eduardo Adenesky-Filho; et al. (Quaternary Science Reviews, 2025)

Around the World in 26 Million Years: Diversification and Biogeography of Pantropical Grass‐Yellow Eurema Butterflies (Pieridae: Coliadinae) - Jing V. Leong; Pável Matos‐Maraví; Rayner Núñez; Renato Nunes; Weijun Liang; Michael F. Braby; Tenzing Doleck; Kwaku Aduse‐Poku; Yutaka Inayoshi; Yu‐Feng Hsu; Niklas Wahlberg; Djunijanti Peggie; et al. (Journal of Biogeography, 2025)
Aim Grass‐yellow butterflies ( Eurema ) are a group of pantropical Pieridae distributed throughout Asia, Australasia, Africa and the New World. However, little is known about their diversification, including the biogeographic mechanism(s) explaining their circumglobal distribution. We present the first densely sampled, time‐calibrated phylogeny and biogeographic reconstruction of grass‐yellows to confirm the monophyly of the genera, re‐evaluate their taxonomy and infer the biogeographic events contributing to their worldwide distribution. Location Global tropics and subtropics. Taxon The butterfly tribe Euremini (Pieridae: Coliadinae). Methods We analysed up to 391 genetic loci from 126 samples of 66 ingroup species. Divergence dating was accomplished in a Bayesian phylogenetic framework using secondary calibration points, and maximum likelihood models of various biogeographic models were fitted to the data using the R package BioGeoBEARS. We used the best fitting model to estimate relative dispersal events with biogeographical stochastic mapping. Finally, we estimated branch‐specific speciation and extinction rates to assess the diversification history of the group. Results Different phylogenomic analyses converged on similar topologies with robust support. Grass‐yellows emerged ca . 26 Mya in the New World, and a single extant lineage dispersed to Asia in the early Miocene, where they diversified and dispersed to Africa and Australasia. The fastest rates of diversification occurred in the Old World tropics during the late Miocene. Many of the grass‐yellow genera were either paraphyletic or polyphyletic as traditionally circumscribed. To maintain nomenclatural stability, we place all grass‐yellows in Eurema sensu lato and recognise two subgenera: Eurema ( Abaeis ) and Eurema ( Eurema ). Main Conclusions Grass‐yellow butterflies originated in the Americas and attained their global distributional patterns via dispersal. The Indo‐Australian and Caribbean archipelagoes seem to have accelerated the diversification of the group, and movement in and out of these island regions was frequent. Although the traditional view of founder‐event speciation envisions migrants from large landmasses (‘mainland’) colonising smaller landmasses (‘islands’), we find that island to mainland dispersal and differentiation were equally or more common.

Relief determines patterns of structure and composition of tree vegetation in seasonal forests in the Brazilian Cerrado - Maxwell R. Oliveira; Francielli Bao; Evaldo B. Souza; Arnildo Pott; Rosa H. Silva; Pedro Isaac; Joanice Lube Battilani; Vivian Ribeiro Baptista Maria; Edna Scremin-Dias; Vali Joana Pott; Alexandre de Matos Martins Pereira; Geraldo A. Damasceno Junior (Brazilian Journal of Botany, 2025)

Graphene-like biochars from pyrolysis of sugarcane bagasse and exhausted black acacia bark for the production of supercapacitors - Mayara R. Fornari; Bruna M. Hryniewicz; Tassya T.S. Matos; Juliana Schultz; Marcio Vidotti; Antonio S. Mangrich (Biomass and Bioenergy, 2025)

Cross-cultural differences and acculturation in affective response and sensory perception: a case study across Chinese immigrants and local consumers in New Zealand - Amanda Dupas de Matos; Ao Chen; Robyn Maggs; A. Jonathan R. Godfrey; Maheeka Weerawarna N.R.P.; Joanne Hort (Food Quality and Preference, 2025)

Plasma miRNAs Correlate with Structural Brain and Cardiac Damage in Friedreich’s Ataxia - Thiago M. Peluzzo; André S. Vieira; Alexandre H. B. Matos; Cynthia Silveira; Mariana Martin; Otávio R. C. Filho; Thiago J.R. Rezende; Alberto R. M. Martinez; Marcondes C. França (The Cerebellum, 2024)

Investigating multiple vegetable oils and recycled variant for microplastics extraction from water, integrated with Raman spectroscopy - R. Garzón-Vidueira; D. Rede; R. Rial-Otero; R. Vilarinho; J.A. Moreira; S. Jorge; M. André; R. Barbosa; C. Delerue-Matos; V. Cruz Fernandes (Science of The Total Environment, 2024)

Voltammetric immunosensor based on oxidized carbon nanotubes/MnFe2O4 hybrid nanoplatform for amplified detection of celery (Apium graveolens) - Joana S. Teixeira; Maria Freitas; Catarina Oliveira; Clara R. Pereira; Cristina Delerue-Matos; Henri P.A. Nouws (Food Chemistry, 2024)

Prospecting for New Potential Biocontrol Agents Against Colletotrichum lindemuthianum, the Causal Agent of Bean Anthracnose - Rosilene C. Matos; Sibele A. da Silva; Isabella F. Cordeiro; Angélica B. Sanchez; Maria R. A. Damasceno; Lorrana C. M. Rocha; Gustavo S. Kajitani; Josino José Barbosa; Marisa V. de Queiroz; Camila Carrião Machado Garcia; Leandro M. Moreira (Journal of Soil Science and Plant Nutrition, 2024)

Unsupervised segmentation for sandstone thin section image analysis - Rayan T. C. M. Barbosa; E. L. Faria; Matheus Klatt; Thais C. Silva; Juliana. M. Coelho; Thais F. Matos; Bernardo C. C. Santos; J. L. Gonzalez; Clécio R. Bom; Márcio P. de Albuquerque; Marcelo P. de Albuquerque (Computational Geosciences, 2024)

Quantifying spatially explicit uncertainty in empirically downscaled climate data - Nicole C. Inglis; Taylor R. Brown; Ashley B. Cale; Theodore Hartsook; Adriano Matos; Johanson Onyegbula; Jonathan A. Greenberg (International Journal of Climatology, 2024)
Ecological simulations including forest and vegetation growth models require climate inputs that match the resolution and extent of the process being modelled. Climate inputs are often derived at resolutions coarser than the scale of many ecosystem processes. Machine learning models can be trained to spatially downscale climate data to fine (30 m) resolution using topographic variables such as elevation, aspect and other site‐specific factors. Statistically downscaled climate models will have spatially varying uncertainty that is not usually incorporated into downscaling techniques for error propagation into later models, are often applied on smaller areas, are not fine enough resolutions for many modelling techniques, or are not always scalable to large spatial extents. There remains opportunity to leverage machine learning advancements to downscale climate to very fine (30 m) resolutions with associated spatially explicit uncertainty to represent microclimatic variation in ecological models. In this study, we used quantile machine learning to produce 30 m downscaled temperature and precipitation data and associated model prediction uncertainty for the state of California. Temperature models were accurate at downscaling 4 km climate data to 30 m, performing better than the 4 km data at high and low slope positions and at high elevations, especially where there were fewer weather observations. Precipitation model predictions did not show global improvement over the 4 km scale, but were more accurate at high elevations, slopes with higher solar radiation and in valleys. For all climate variables, the added detail of spatial explicit uncertainty via 90% prediction intervals provides critical insight into the utility of empirically downscaled climate. The resulting 30 m spatially contiguous outputs can be used as ecological model inputs with uncertainty propagation, to illuminate climate trends over time as a function of fine‐scale spatial factors, and to highlight areas of spatially explicit uncertainty.

Disentangling the veil line for Brazilian biodiversity: An overview from two long-term research programs reveals huge gaps in ecological data reporting - Aretha Franklin Guimaraes; Luciano Carramaschi de Alagao Querido; Taina Rocha; Domingos de Jesus Rodrigues; Pedro Lage Viana; Helena de Godoy Bergallo; Geraldo Wilson Fernandes; Tiago Shizen Pacheco Toma; Helena Streit; Gerhard Ernst Overbeck; Alberico Queiroz Salgueiro de Souza; Albertina Pimentel Lima; et al. (Science of The Total Environment, 2024)

Comparative life cycle assessment of non-thermal plasma for the removal of pharmaceuticals from wastewater - E. Surra; P. Paíga; I. Baptista; R. Jorge; L. Marinheiro; S. Löblich; C. Delerue-Matos (Journal of Environmental Management, 2024)

Hydrothermal silicification along rift border faults in the Rio do Peixe basin, Brazil - Ingrid B. Maciel; Fabrizio Balsamo; Francisco H.R. Bezerra; Francisco C.C. Nogueira; Luigi R. Berio; José A. Brod; Zorano S. Souza; Hannah L.S. Matos-Pimentel; Bruno R.B.M. Carvalho; Jorge A.B. Souza (Marine and Petroleum Geology, 2024)

Soil carbon stock changes in a crop-livestock-forestry integration in Southern Goiás State, Brazil - B. E. Madari; P. S. Matos; J. M. Oliveira; M. T. M. Carvalho; A. L. R. Silveira; P. L. O. A. Machado; W. A. Araujo; M. M. B. Siqueira; T. M. Ferraresi; F. M. C. Freitas; P. V. Rizzo; R. R. Silva; et al. (Agroforestry Systems, 2024)

P15-15 Unveiling the therapeutic potential of MSC-derived conditioned media and exosomes towards COVID-19-induced neurological sequelae - C.M. Trigo; S.P. Camões; A.S. Serras; A.T. Matos; R. Vitorino; A.R. Vaz; D. Brites; S. Solá; J.P. Miranda (Toxicology Letters, 2024)

Do endocrine disrupting compounds impact earthworms? A comprehensive evidence review - Tiago Azevedo; Mariana Gonçalves; Rita Silva-Reis; Beatriz Medeiros-Fonseca; Marta Roboredo; João R. Sousa; Paula A. Oliveira; Maria de Lurdes Pinto; Francisco Peixoto; Isabel Gaivão; Manuela Matos; Ana M. Coimbra (Reviews in Environmental Science and Bio/Technology, 2024)
Endocrine-disrupting compounds (EDCs) are ubiquitous in soil, posing serious risks to soil biota, especially earthworms, which have been found to be affected by these compounds, despite not being their typical target organisms. Earthworms are essential for sustaining soil health and quality, by promoting soil aeration, organic matter decomposition and nutrient cycling, among other functions. This review synthesizes available literature evidencing the negative impact of EDC exposure, through traditional endocrine pathways and other toxicological mechanisms, on histopathological, biochemical, molecular and reproductive endpoints of earthworms. The compounds described, in the consulted literature, to induce histopathological, biochemical, genotoxicity and molecular and reproductive alterations include antibiotics, antimicrobial additives, flame retardants, fragrances, fungicides, herbicides, hormones, inorganic ions, insecticides, organic UV filters, parabens, perfluoroalkyl substances, pesticides, petroleum derivatives, plasticizers and polychlorinated biphenyls. These compounds reach soil through direct application or via contaminated organic amendments and water derived from potentially polluted sources. The findings gather in the present review highlight the vulnerability of earthworms to a broad spectrum of chemicals with endocrine disrupting capacity. Additionally, these studies emphasize the physiological disruptions caused by EDC exposure, underscoring the critical need to protect biodiversity, including earthworms, to ensure soil quality and ecosystem sustainability. Ongoing research has provided insights into molecular mechanisms responsive to EDCs in earthworms, including the identification of putative hormone receptors that exhibit functional similarity to those present in vertebrates. In conclusion, this review emphasizes the impact of EDCs in earthworms, especially through non-hormonal mediated pathways, and addresses the need for strong regulatory frameworks to mitigate the detrimental effects of EDCs on soil invertebrates in order to safeguard soil ecosystems. Graphical abstract

Novel 3D electro-Fenton reactor based on a catalytic packed bed reactor of perovskite/carbon microelectrodes for the removal of carbamazepine in wastewater - A. Cruz del Álamo; A. Puga; C.M. Dias Soares; M.I. Pariente; M. Pazos; R. Molina; M.A. Sanromán; F. Martínez; C. Delerue-Matos (Journal of Environmental Chemical Engineering, 2024)

Molecular evidence of sporadic Coxiella burnetii excretion in sheep milk, central Portugal - Humberto Pires; Sérgio Santos-Silva; Andreia V.S. Cruz; Luís Cardoso; Ana Patrícia Lopes; Maria A. Pereira; Carmen Nóbrega; Ana Cristina Mega; Carla Santos; Rita Cruz; Fernando Esteves; Helena Vala; et al. (Veterinary Research Communications, 2024)
Coxiella burnetii is the etiologic agent of Q fever, a worldwide zoonosis. Cattle, sheep and goats are considered the main reservoirs of the disease. Transmission to humans occurs mainly through the inhalation of infectious aerosols from milk, faeces, urine, and birth products from infected ruminants. In this study, a 2-year longitudinal approach was performed to ascertain the excretion of C. burnetii in bulk tank milk samples of sheep from a mountain plateau in central Portugal, with sampling conducted during the years 2015 and 2016. From a total of 156 bulk tank milk samples tested by qPCR, only one showed to be positive for C. burnetii (1.28% [95%CI: 0.03–6.94]), from 2015, the first year of collection. Bidirectional sequencing and phylogenetic analysis of IS1111 transposase partial region confirmed the presence of C. burnetii DNA. The presence of C. burnetii in raw milk samples highlights the necessity for additional research to determine if raw milk is a potential source for human infection. Animal health surveillance and prevention measures against this zoonotic disease should be considered.

Invasive non-native species in Brazil: an updated overview - Rafael D. Zenni; Sílvia R. Ziller; Clarissa A. da Rosa; Rafael B. Sühs; Patricia B. Puechagut; Beloni T. P. Marterer; Gustavo Heringer; Ana Carolina L. de Matos; Marina L. Bueno; Jonathan W. Almeida; Carlos H. T. Silva; José Renato Legracie-Júnior; et al. (Biological Invasions, 2024)

Correction to: The net-tube caddisflies (Trichoptera: Psychomyioidea: Xiphocentronidae) from the Brazilian Amazon: discovery of new species and reports of new distributional records - Gleison R. Desidério; Albane Vilarino; Laissa S. Santos; Marcos A. R. Pires; Ana M. Pes; Talissa Matos; Karina Dias-Silva; Neusa Hamada (Biologia, 2024)

A review of methods and instruments to monitor turbidity and suspended sediment concentration - T. Matos; M.S. Martins; R. Henriques; L.M. Goncalves (Journal of Water Process Engineering, 2024)

Geography and ecology shape the phylogenetic composition of Amazonian tree communities - Bruno Garcia Luize; David Bauman; Hans ter Steege; Clarisse Palma‐Silva; Iêda Leão do Amaral; Luiz de Souza Coelho; Francisca Dionízia de Almeida Matos; Diógenes de Andrade Lima Filho; Rafael P. Salomão; Florian Wittmann; Carolina V. Castilho; Marcelo de Jesus Veiga Carim; et al. (Journal of Biogeography, 2024)
Aim Amazonia hosts more tree species from numerous evolutionary lineages, both young and ancient, than any other biogeographic region. Previous studies have shown that tree lineages colonized multiple edaphic environments and dispersed widely across Amazonia, leading to a hypothesis, which we test, that lineages should not be strongly associated with either geographic regions or edaphic forest types. Location Amazonia. Taxon Angiosperms (Magnoliids; Monocots; Eudicots). Methods Data for the abundance of 5082 tree species in 1989 plots were combined with a mega‐phylogeny. We applied evolutionary ordination to assess how phylogenetic composition varies across Amazonia. We used variation partitioning and Moran's eigenvector maps (MEM) to test and quantify the separate and joint contributions of spatial and environmental variables to explain the phylogenetic composition of plots. We tested the indicator value of lineages for geographic regions and edaphic forest types and mapped associations onto the phylogeny. Results In the terra firme and várzea forest types, the phylogenetic composition varies by geographic region, but the igapó and white‐sand forest types retain a unique evolutionary signature regardless of region. Overall, we find that soil chemistry, climate and topography explain 24% of the variation in phylogenetic composition, with 79% of that variation being spatially structured ( R 2 = 19% overall for combined spatial/environmental effects). The phylogenetic composition also shows substantial spatial patterns not related to the environmental variables we quantified ( R 2 = 28%). A greater number of lineages were significant indicators of geographic regions than forest types. Main Conclusion Numerous tree lineages, including some ancient ones (>66 Ma), show strong associations with geographic regions and edaphic forest types of Amazonia. This shows that specialization in specific edaphic environments has played a long‐standing role in the evolutionary assembly of Amazonian forests. Furthermore, many lineages, even those that have dispersed across Amazonia, dominate within a specific region, likely because of phylogenetically conserved niches for environmental conditions that are prevalent within regions.

The net-tube caddisflies (Trichoptera: Psychomyioidea: Xiphocentronidae) from the Brazilian Amazon: discovery of new species and reports of new distributional records - Gleison R. Desidério; Albane Vilarino; Laissa S. Santos; Marcos A. R. Pires; Ana M. Pes; Talissa Matos; Karina Dias-Silva; Neusa Hamada (Biologia, 2024)

Transcriptome profiling of the posterior salivary glands of the cuttlefish Sepia officinalis from the Portuguese West coast - Cátia Gonçalves; Inês Moutinho Cabral; António P. Alves de Matos; Ana R. Grosso; Pedro M. Costa (Frontiers in Marine Science, 2024)
Cephalopods like octopuses and cuttlefishes are known to secrete a ‘toxic saliva’ to inject into their prey, especially crustaceans since the XIX century. However, only in the mid-XX century were the first coleoid-specific toxins successfully isolated. Motivated by the growing interest on the global ocean as an almost inexhaustible source of novel bioactive compounds, we used RNA-Seq – based transcriptomics and de novo assembly of transcriptomes to screen the posterior salivary glands of Sepia officinalis (the common cuttlefish) from the Portuguese West coast for toxins and other bioactive proteins and peptides. Supported by microanatomical analyses, the posterior salivary glands constitute indeed the ‘venom gland’ whereas the more elusive anterior salivary glands (embedded in the buccal mass) are responsible for the production of mucin-rich saliva that is effectively the vehicle that transports the toxins as the venom is injected into the prey. Indeed, the transcriptomic profiling suggests that the cuttlefish venom is complex mixture of bioactive proteins, among which neurotoxins are major players, together with enzymes whose function is to digest the extracellular matrix to facilitate diffusion of the toxins. Nonetheless, by comparing with previous RNA-Seq data obtained from S. officinalis collected from other biogeographical areas, it may be suggested that significant inter-populational variation in venom composition can occur, which may potentially increase the span of bioactives secreted by these animals. We isolated and validated the full coding sequences for three important toxins, a cysteine-rich venom protein (CRVP), a venom insulin (VIns) and a cephalotoxin (CTX). The toxins seem to be relatively conserved among coleoids but diverging from other venomous mollusks such as cone snails. Their properties as potent modulators of glucose (in the case of VIns) and as potential neurotoxins (like CRVP and CTX) can render them primer targets for drug development.

Antimicrobial resistance patterns of Staphylococcus spp. isolated from clinical specimens of companion animals in Northern Portugal, 2021–2023 - D. Araújo; R. Oliveira; B.L. Silva; J. Castro; C. Ramos; F. Matos; C. Almeida; S. Silva (The Veterinary Journal, 2024)

Feedback facilitation by adenosine A2A receptors of ATP release from mouse hippocampal nerve terminals - Francisco Q. Gonçalves; Pedro Valada; Marco Matos; Rodrigo A. Cunha; Angelo R. Tomé (Purinergic Signalling, 2024)
The adenosine modulation system is mostly composed by inhibitory A 1 receptors (A 1 R) and the less abundant facilitatory A 2A receptors (A 2A R), the latter selectively engaged at high frequency stimulation associated with synaptic plasticity processes in the hippocampus. A 2A R are activated by adenosine originated from extracellular ATP through ecto-5’-nucleotidase or CD73-mediated catabolism. Using hippocampal synaptosomes, we now investigated how adenosine receptors modulate the synaptic release of ATP. The A 2A R agonist CGS21680 (10-100 nM) enhanced the K + -evoked release of ATP, whereas both SCH58261 and the CD73 inhibitor α,β-methylene ADP (100 μM) decreased ATP release; all these effects were abolished in forebrain A 2A R knockout mice. The A 1 R agonist CPA (10-100 nM) inhibited ATP release, whereas the A 1 R antagonist DPCPX (100 nM) was devoid of effects. The presence of SCH58261 potentiated CPA-mediated ATP release and uncovered a facilitatory effect of DPCPX. Overall, these findings indicate that ATP release is predominantly controlled by A 2A R, which are involved in an apparent feedback loop of A 2A R-mediated increased ATP release together with dampening of A 1 R-mediated inhibition. This study is a tribute to María Teresa Miras-Portugal.

Comparison between commercial media and TRIS-egg yolk extender in the refrigerated storage of collared peccary semen at 17 °C - Romário P. Santos; Samara S.J. Moreira; Luana G.P. Bezerra; Yasmim C.S. Cavalcante; Ana G. Pereira; Tayná M. Matos; Moacir F. Oliveira; Alexandre R. Silva (Animal Reproduction Science, 2024)

Origin of rare earth elements in acid mine drainage traced by strontium and neodymium isotopes - Rafael León; Francisco Macías; Carlos R. Cánovas; Ricardo Millán-Becerro; Jonatan Romero-Matos; José Miguel Nieto (Geochimica et Cosmochimica Acta, 2024)

Camera trap surveys of A tlantic F orest mammals: A data set for analyses considering imperfect detection (2004–2020) - Ingridi Camboim Franceschi; Rubem Augusto da Paixão Dornas; Isabel Salgueiro Lermen; Artur Vicente Pfeifer Coelho; Ademir Henrique Vilas Boas; Adriano Garcia Chiarello; Adriano Pereira Paglia; Agnis Cristiane de Souza; Alana Rafaela Borsekowsky; Alessandro Rocha; Alex Bager; Alexander Zaidan de Souza; et al. (Ecology, 2024)
Camera traps became the main observational method of a myriad of species over large areas. Data sets from camera traps can be used to describe the patterns and monitor the occupancy, abundance, and richness of wildlife, essential information for conservation in times of rapid climate and land‐cover changes. Habitat loss and poaching are responsible for historical population losses of mammals in the Atlantic Forest biodiversity hotspot, especially for medium to large‐sized species. Here we present a data set from camera trap surveys of medium to large‐sized native mammals (>1 kg) across the Atlantic Forest. We compiled data from 5380 ground‐level camera trap deployments in 3046 locations, from 2004 to 2020, resulting in 43,068 records of 58 species. These data add to existing data sets of mammals in the Atlantic Forest by including dates of camera operation needed for analyses dealing with imperfect detection. We also included, when available, information on important predictors of detection, namely the camera brand and model, use of bait, and obstruction of camera viewshed that can be measured from example pictures at each camera location. Besides its application in studies on the patterns and mechanisms behind occupancy, relative abundance, richness, and detection, the data set presented here can be used to study species' daily activity patterns, activity levels, and spatiotemporal interactions between species. Moreover, data can be used combined with other data sources in the multiple and expanding uses of integrated population modeling. An R script is available to view summaries of the data set. We expect that this data set will be used to advance the knowledge of mammal assemblages and to inform evidence‐based solutions for the conservation of the Atlantic Forest. The data are not copyright restricted; please cite this paper when using the data.

An empirical DNA-based identification of morphologically similar snappers (Lutjanus campechanus, Lutjanus purpureus) using a versatile bioinformatics workflow for the discovery and analysis of informative single-nucleotide polymorphisms - Robert A. Literman; Mayara P. V. Matos; Sara M. Handy; Jonathan R. Deeds (Frontiers in Marine Science, 2024)
The commercially important species Lutjanus campechanus (Northern/Gulf red snapper) and Lutjanus purpureus (Southern/Caribbean red snapper) are the protagonists of a decade’s long taxonomic debate over their species delimitation, due in part to partial habitat overlap, extensive morphological similarity, and the lack of resolution when applying canonically reliable DNA barcoding approaches. In this study, we leveraged publicly available RAD-Seq data for L. campechanus and L. purpureus to identify species-informative single‐nucleotide polymorphisms (SNPs) at the genome scale that were successful in distinguishing the Northern and Southern red snappers, while also detecting individuals exhibiting introgression. This 4-step empirical approach demonstrates the value of applying novel bioinformatics pipelines to existing genome-scale data to maximize the distillation of informative subsets. Our results facilitate economically relevant species identification in addition to confirming or challenging species identifications for specimens with data in public databases. These findings and their applications will benefit future sustainability strategies and broader research questions surrounding these overfished and evolutionarily entangled snapper species.

Sensory characteristics of plant-based milk alternatives: Product characterisation by consumers and drivers of liking - Sara R. Jaeger; Amanda Dupas de Matos; Ama Frempomaa Oduro; Joanne Hort (Food Research International, 2024)

Detrimental impact of a heatwave on male reproductive behaviour and fertility - Afonso Grandela; Marta A. Antunes; Marta A. Santos; Margarida Matos; Leonor R. Rodrigues; Pedro Simões (acta ethologica, 2024)
Understanding how heatwaves impact on different aspects of mating behaviour and fertility is getting increasingly important. In this context, laboratory fertility and mating experiments involving manipulation and exposure of insects to different thermal conditions are common procedures. To conduct such experiments practical methods such as dyes are needed for an easy, non-invasive discrimination of individuals. We report here a study measuring the effect of an extended heat stress applied to males on several parameters of mating behaviour and fertility of laboratory populations of Drosophila subobscura derived from two distinct European locations. We found highly detrimental effects of heatwave on mating behaviour—with longer (courtship and copulation) latencies and lower mating occurrence but no changes in mating duration—and fertility, with reduced fecundity and reproductive success. Furthermore, we also tested the efficacy of food dye as a marker for individual discrimination and mating occurrence. While food dye did not allow to infer the occurrence of a mating based on a transfer of coloration from male to female, it did not affect mating and fertility, attesting its utility has a method for discriminating individuals within mating experiments in the context of thermal studies. Importantly, despite the fact that the heatwave was only applied in males, we observed an impact on behaviour of females that mated with stressed males, by often refusing their nuptial feeding. This opens possibilities for further integrated research on the changes of female and male mating behaviour and fertility under different thermal scenarios.

Gone with the stream: Functional connectivity of a cold‐water coral at basin scale - Fábio L. Matos; Jacopo Aguzzi; Joan B. Company; Marina R. Cunha (Limnology and Oceanography, 2024)
Lophelia pertusa reefs are vulnerable deep‐sea ecosystems and their ecological integrity partly depends on the connectivity and availability of suitable habitat. Moreover, connectivity is a guiding principle in marine conservation planning, particularly for spatial prioritization and for the design of networks of marine protected areas. We estimated the functional seascape connectivity of L. pertusa in the Mediterranean Sea and provide a framework for prioritizing habitat areas for the species conservation. These goals were achieved by simulating transport and potential dispersal of virtual larvae using biophysical modeling and assessing habitat availability based on the suitability and spatial arrangement of the seascape and inter‐annual climatological variability. Habitat availability was estimated using a network analysis and accounting for the attributes of habitat areas (i.e., size and quality). The connectivity among Mediterranean ecoregions was weak and an increase in the frequency of climate‐driven events (e.g., dense shelf water cascading) may worsen this scenario. However, the potential exchange of larvae between patches within the same ecoregion was high, favoring populations resilience to local disturbances. The analysis of habitat availability allowed identifying important habitat areas for the connectivity of the L. pertusa including the Gulf of Lion, the Apulian and Sicily Island continental margin. Some of the habitat areas identified as important for the connectivity of the L. pertusa are exposed to intense anthropogenic pressures, that may act synergistically with climate change imposing greater challenges to species conservation. These habitat areas may be prioritized in future management and conservation actions targeting L. pertusa .

Melatonin acts through different mechanisms to control oxidative stress and primordial follicle activation and survival during in vitro culture of bovine ovarian tissue - Bianca R. Silva; Francisco C. Costa; Miguel F. De Lima Neto; Francisco F. Caetano Filho; Ernando I.T. de Assis; Francisco L.N. Aguiar; Anderson W.B. Silva; Solano D. Martins; Valdevane R. Araújo; Maria H.T. Matos; José J.N. Costa; José R.V. Silva (Domestic Animal Endocrinology, 2024)

Culture operational strategies for the production of methane and algal oil using ethanol vinasse effluent - Gabriele R. Conceição; Carine S. da Silva; Tatiana O. do Vale; Jacson N. dos Santos; Josilene B. T. L. Matos; Paulo F.de Almeida; Fabio A. Chinalia (Journal of Applied Phycology, 2023)

P23-05: Urinary monohydroxyl-polycyclic aromatic hydrocarbons and metals in firefighters with active participation in controlled structure fires - J. Teixeira; R. Azevedo; A. Almeida; F. Rodrigues; A. Santos-Silva; C. Delerue-Matos; M. Oliveira (Toxicology Letters, 2023)

Giants of the Amazon: How does environmental variation drive the diversity patterns of large trees? - Robson Borges de Lima; Eric Bastos Görgens; Diego Armando S. da Silva; Cinthia Pereira de Oliveira; Anderson Pedro B. Batista; Rinaldo L. Caraciolo Ferreira; Flavia R. C. Costa; Renato A. Ferreira de Lima; Perseu da Silva Aparício; Jadson Coelho de Abreu; José Antônio Aleixo da Silva; Aretha Franklin Guimaraes; et al. (Global Change Biology, 2023)
For more than three decades, major efforts in sampling and analyzing tree diversity in South America have focused almost exclusively on trees with stems of at least 10 and 2.5 cm diameter, showing highest species diversity in the wetter western and northern Amazon forests. By contrast, little attention has been paid to patterns and drivers of diversity in the largest canopy and emergent trees, which is surprising given these have dominant ecological functions. Here, we use a machine learning approach to quantify the importance of environmental factors and apply it to generate spatial predictions of the species diversity of all trees (dbh ≥ 10 cm) and for very large trees (dbh ≥ 70 cm) using data from 243 forest plots (108,450 trees and 2832 species) distributed across different forest types and biogeographic regions of the Brazilian Amazon. The diversity of large trees and of all trees was significantly associated with three environmental factors, but in contrasting ways across regions and forest types. Environmental variables associated with disturbances, for example, the lightning flash rate and wind speed, as well as the fraction of photosynthetically active radiation, tend to govern the diversity of large trees. Upland rainforests in the Guiana Shield and Roraima regions had a high diversity of large trees. By contrast, variables associated with resources tend to govern tree diversity in general. Places such as the province of Imeri and the northern portion of the province of Madeira stand out for their high diversity of species in general. Climatic and topographic stability and functional adaptation mechanisms promote ideal conditions for species diversity. Finally, we mapped general patterns of tree species diversity in the Brazilian Amazon, which differ substantially depending on size class.

Data on vegetation across forest edges from the FERN ( F orest E dge R esearch N etwork) - Karen A. Harper; Logan Gray; S. Ellen Macdonald; Daniel Lesieur; Danielle DeFields; Pavel Dodonov; Caroline Mary Adrianne Franklin; Sean R. Haughian; Liliana Mascarúa López; Alexandra Heathcote; Krista Jager; Renee Yang; et al. (Ecology, 2023)
Many studies have focused on vegetation across forest edges to study impacts of edges created by human activities on forest structure and composition, or patterns of vegetation at inherent natural edges. Our objective was to create a database of plant‐related variables across different types of edges from various studies (mainly from across Canada, but also in Brazil and Belize) to facilitate edge research. We compiled data on vegetation along more than 300 transects perpendicular to forest edges adjacent to clear‐cuts, burned areas, bogs, lakes, barrens, insect disturbances, and riparian areas from 24 studies conducted over the past three decades. Data were compiled for more than 400 plant species and forest structure variables (e.g., trees, logs, canopy cover). All data were collected with a similar sampling design of quadrats along transects perpendicular to forest edges, but with varying numbers of transects and quadrats, and distances from the edge. The purpose for most of the studies was either to determine the distance of edge influence (edge width) or to explore the pattern of vegetation along the edge to interior gradient. We provide data tables for the cover of plant species and functional groups, the species and size of live and dead trees, the density of saplings, maximum height of functional groups and shrub species, and the cover of functional groups at different heights (vertical distribution of vegetation). The Forest Edge Research Network (FERN) database provides extensive data on many variables that can be used for further study including meta‐analyses and can assist in answering questions important to conservation efforts (e.g., how is distance of edge influence from created edges affected by different factors?). We plan to expand this database with subsequent studies from the authors and we invite others to contribute to make this a more global database. The data are released under a CC0 license. When using these data, we ask that you cite this data paper and any relevant publications listed in our metadata file. We also encourage you to contact the first author if you are planning to use or contribute to this database.

Bioactivity of plant extracts against Atta sexdens (Hymenoptera: Formicidae) workers by ingestion - Flávia Vidal Teixeira; Talytha R. de Melo Souza; Maria A. Castellani; Roberto da Silva Camargo; Luiz C. Forti; Vanderlucia F. de Paula; Aline Silva; Carlos Alberto O. de Matos; Óscar B. Nipato; Aldenise Alves Moreira; Julian Alberto Sabattini (International Journal of Tropical Insect Science, 2023)

Exploring the prevalence and antibiotic resistance profile of Klebsiella pneumoniae and Klebsiella oxytoca isolated from clinically ill companion animals from North of Portugal - D. Araújo; J. Castro; F. Matos; R. Oliveira; C. Ramos; C. Almeida; S. Silva (Research in Veterinary Science, 2023)

Wildfire effects on the hydrogeochemistry of a river severely polluted by acid mine drainage - Jonatan Romero-Matos; Carlos R. Cánovas; Francisco Macías; Rafael Pérez-López; Rafael León; Ricardo Millán-Becerro; Jose Miguel Nieto (Water Research, 2023)

The phylogenomics and evolutionary dynamics of the organellar genomes in carnivorous Utricularia and Genlisea species (Lentibulariaceae) - Saura R. Silva; Vitor F.O. Miranda; Todd P. Michael; Bartosz J. Płachno; Ramon G. Matos; Lubomir Adamec; Sergei L.K. Pond; Alexander G. Lucaci; Daniel G. Pinheiro; Alessandro M. Varani (Molecular Phylogenetics and Evolution, 2023)

Evidence of SARS-CoV-2 infection in postmortem lung, kidney, and liver samples, revealing cellular targets involved in COVID-19 pathogenesis - Viviana Falcón-Cama; Teresita Montero-González; Emilio F. Acosta-Medina; Gerardo Guillen-Nieto; Jorge Berlanga-Acosta; Celia Fernández-Ortega; Anabel Alfonso-Falcón; Nathalie Gilva-Rodríguez; Lilianne López-Nocedo; Daina Cremata-García; Mariuska Matos-Terrero; Giselle Pentón-Rol; et al. (Archives of Virology, 2023)
There is an urgent need to understand severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2)-host interactions involved in virus spread and pathogenesis, which might contribute to the identification of new therapeutic targets. In this study, we investigated the presence of SARS-CoV-2 in postmortem lung, kidney, and liver samples of patients who died with coronavirus disease (COVID-19) and its relationship with host factors involved in virus spread and pathogenesis, using microscopy-based methods. The cases analyzed showed advanced stages of diffuse acute alveolar damage and fibrosis. We identified the SARS-CoV-2 nucleocapsid (NC) in a variety of cells, colocalizing with mitochondrial proteins, lipid droplets (LDs), and key host proteins that have been implicated in inflammation, tissue repair, and the SARS-CoV-2 life cycle (vimentin, NLRP3, fibronectin, LC3B, DDX3X, and PPARγ), pointing to vimentin and LDs as platforms involved not only in the viral life cycle but also in inflammation and pathogenesis. SARS-CoV-2 isolated from a patient´s nasal swab was grown in cell culture and used to infect hamsters. Target cells identified in human tissue samples included lung epithelial and endothelial cells; lipogenic fibroblast-like cells (FLCs) showing features of lipofibroblasts such as activated PPARγ signaling and LDs; lung FLCs expressing fibronectin and vimentin and macrophages, both with evidence of NLRP3- and IL1β-induced responses; regulatory cells expressing immune-checkpoint proteins involved in lung repair responses and contributing to inflammatory responses in the lung; CD34 + liver endothelial cells and hepatocytes expressing vimentin; renal interstitial cells; and the juxtaglomerular apparatus. This suggests that SARS-CoV-2 may directly interfere with critical lung, renal, and liver functions involved in COVID-19-pathogenesis.

Geographic patterns of tree dispersal modes in Amazonia and their ecological correlates - Diego F. Correa; Pablo R. Stevenson; Maria Natalia Umaña; Luiz de Souza Coelho; Diógenes de Andrade Lima Filho; Rafael P. Salomão; Iêda Leão do Amaral; Florian Wittmann; Francisca Dionízia de Almeida Matos; Carolina V. Castilho; Oliver L. Phillips; Juan Ernesto Guevara; et al. (Global Ecology and Biogeography, 2023)
Aim To investigate the geographic patterns and ecological correlates in the geographic distribution of the most common tree dispersal modes in Amazonia (endozoochory, synzoochory, anemochory and hydrochory). We examined if the proportional abundance of these dispersal modes could be explained by the availability of dispersal agents (disperser‐availability hypothesis) and/or the availability of resources for constructing zoochorous fruits (resource‐availability hypothesis). Time period Tree‐inventory plots established between 1934 and 2019. Major taxa studied Trees with a diameter at breast height (DBH) ≥ 9.55 cm. Location Amazonia, here defined as the lowland rain forests of the Amazon River basin and the Guiana Shield. Methods We assigned dispersal modes to a total of 5433 species and morphospecies within 1877 tree‐inventory plots across terra‐firme, seasonally flooded, and permanently flooded forests. We investigated geographic patterns in the proportional abundance of dispersal modes. We performed an abundance‐weighted mean pairwise distance (MPD) test and fit generalized linear models (GLMs) to explain the geographic distribution of dispersal modes. Results Anemochory was significantly, positively associated with mean annual wind speed, and hydrochory was significantly higher in flooded forests. Dispersal modes did not consistently show significant associations with the availability of resources for constructing zoochorous fruits. A lower dissimilarity in dispersal modes, resulting from a higher dominance of endozoochory, occurred in terra‐firme forests (excluding podzols) compared to flooded forests. Main conclusions The disperser‐availability hypothesis was well supported for abiotic dispersal modes (anemochory and hydrochory). The availability of resources for constructing zoochorous fruits seems an unlikely explanation for the distribution of dispersal modes in Amazonia. The association between frugivores and the proportional abundance of zoochory requires further research, as tree recruitment not only depends on dispersal vectors but also on conditions that favour or limit seedling recruitment across forest types.

Environmental disaster in mining areas: routes of exposure to metals in the Doce River basin - A. R. de Matos; H. T. da Silva; M. C. S. da Faria; B. M. Freire; R. M. Pereira; B. L. Batista; J. L. Rodrigues (International Journal of Environmental Science and Technology, 2022)

Lithology identification in carbonate thin section images of the Brazilian pre-salt reservoirs by the computational vision and deep learning - E. L. Faria; Juliana. M. Coelho; Thais F. Matos; Bernardo C. C. Santos; Willian A. Trevizan; J. L. Gonzalez; Clécio R. Bom; Márcio P. de Albuquerque; Marcelo P. de Albuquerque (Computational Geosciences, 2022)

Sexual segregation in the foraging distribution, behaviour, and trophic niche of the endemic Boyd’s shearwater (Puffinus lherminieri boydi) - Ivo dos Santos; Jaime A. Ramos; Filipe R. Ceia; Isabel Rodrigues; Nathalie Almeida; Stefan Antunes; Ana R. Carreiro; Diana M. Matos; Ricardo J. Lopes; Pedro Geraldes; Vítor H. Paiva (Marine Biology, 2022)

Pleurotus strains with remediation potential to remove toxic metals from Doce River contaminated by Samarco dam mine - M. P. O. Santos; M. V. N. Santos; R. S. Matos; A. S. Van Der Maas; M. C. S. Faria; B. L. Batista; J. L. Rodrigues; C. A. Bomfeti (International Journal of Environmental Science and Technology, 2022)

Bioactive compounds and hepatoprotective effect of Hancornia speciosa gomes fruit juice on acetaminophen-induced hepatotoxicity in vivo - Rosangela S. Santos; Adriano B. Chaves-Filho; Luiz A. S. Silva; Carlos A. B. Garcia; Audrey R. S. T. Silva; Silvio S. Dolabella; Silvânio S. L. da Costa; Sayuri Miyamoto; Humberto R. Matos (Natural Product Research, 2022)

Foraging costs drive within-colony spatial segregation in shearwaters from two contrasting environments in the North Atlantic Ocean - Jorge M. Pereira; Jaime A. Ramos; Nathalie Almeida; Pedro M. Araújo; Filipe R. Ceia; Pedro Geraldes; Ana M. Marques; Diana M. Matos; Isabel Rodrigues; Ivo dos Santos; Vitor H. Paiva (Oecologia, 2022)

Latent effects of intertidal encapsulated development on juvenile fitness of the marine snail Acanthina monodon - L. P. Salas-Yanquin; N. P. Pinilla; A. S. Matos; J. A. Bűchner-Miranda; J. M. Navarro; V. M. Cubillos; J. A. Pechenik; O. R. Chaparro (Marine Biology, 2022)

A comprehensive review on phytochemicals for fatty liver: are they potential adjuvants? - Taís Menezes do Moinho; Sandro Leão Matos; Carla R. O. Carvalho (Journal of Molecular Medicine, 2022)

Production and bioaccessibility of Emiliania huxleyi biomass and bioactivity of its aqueous and ethanolic extracts - B. Vicente; J. Matos; R. Gomes; M. Sapatinha; Cláudia Afonso; T. Rodrigues; A. Amorim; N. M. Bandarra; Carlos Cardoso (Journal of Applied Phycology, 2021)

Improved 4-nitrophenol removal at Ti/RuO2–Sb2O4–TiO2 laser-made anodes - Aline R. Dória; Géssica O. S. Santos; Mariane M. S. Pelegrinelli; Deyvid C. Silva; Danielle B. de Matos; Eliane Bezerra Cavalcanti; Ronaldo S. Silva; Giancarlo R. Salazar-Banda; Katlin I. B. Eguiluz (Environmental Science and Pollution Research, 2021)

The hidden curve behind COVID-19 outbreak: the impact of delay in treatment initiation in cancer patients and how to mitigate the additional risk of dying—the head and neck cancer model - Leandro L. Matos; Carlos Henrique Q. Forster; Gustavo N. Marta; Gilberto Castro Junior; John A. Ridge; Daisy Hirata; Adalberto Miranda-Filho; Ali Hosny; Alvaro Sanabria; Vincent Gregoire; Snehal G. Patel; Johannes J. Fagan; et al. (Cancer Causes & Control, 2021)

Evaluation of chelating and cytoprotective activity of vanillin against the toxic action of mercuric chloride as an alternative for phytoremediation - Joelma P. da Silva; Maria do S. Costa; Fabia F. Campina; Camila F. Bezerra; Thiago S. de Freitas; Amanda K. Sousa; Celestina E. Sobral Souza; Yedda M. L. S. de Matos; Francisco N. Pereira-Junior; Irwim R. A. Menezes; Henrique D. M. Coutinho; Janaína E. Rocha (Environmental Geochemistry and Health, 2021)

Bioactive and nutritional potential of Alaria esculenta and Saccharina latissima - C. Afonso; J. Matos; I. Guarda; A. Gomes-Bispo; R. Gomes; C. Cardoso; S. Gueifão; I. Delgado; I. Coelho; I. Castanheira; N. M. Bandarra (Journal of Applied Phycology, 2021)

Treptacantha abies-marina (S.G. Gmelin) Kützing: Characterization and Application as a Whole Food Ingredient - C. Afonso; I. Guarda; M. Mourato; L.L. Martins; I. Fonseca; R. Gomes; J. Matos; A. Gomes; N.M. Bandarra; C. Cardoso (Journal of Aquatic Food Product Technology, 2020)

NEOTROPICAL CARNIVORES: a data set on carnivore distribution in the Neotropics - Mariana Nagy‐Reis; Júlia Emi de Faria Oshima; Claudia Zukeran Kanda; Francesca Belem Lopes Palmeira; Fabiano Rodrigues de Melo; Ronaldo Gonçalves Morato; Lilian Bonjorne; Marcelo Magioli; Caroline Leuchtenberger; Fabio Rohe; Frederico Gemesio Lemos; Felipe Martello; et al. (Ecology, 2020)
Mammalian carnivores are considered a key group in maintaining ecological health and can indicate potential ecological integrity in landscapes where they occur. Carnivores also hold high conservation value and their habitat requirements can guide management and conservation plans. The order Carnivora has 84 species from 8 families in the Neotropical region: Canidae; Felidae; Mephitidae; Mustelidae; Otariidae; Phocidae; Procyonidae; and Ursidae. Herein, we include published and unpublished data on native terrestrial Neotropical carnivores (Canidae; Felidae; Mephitidae; Mustelidae; Procyonidae; and Ursidae). NEOTROPICAL CARNIVORES is a publicly available data set that includes 99,605 data entries from 35,511 unique georeferenced coordinates. Detection/non‐detection and quantitative data were obtained from 1818 to 2018 by researchers, governmental agencies, non‐governmental organizations, and private consultants. Data were collected using several methods including camera trapping, museum collections, roadkill, line transect, and opportunistic records. Literature (peer‐reviewed and grey literature) from Portuguese, Spanish and English were incorporated in this compilation. Most of the data set consists of detection data entries (n = 79,343; 79.7%) but also includes non‐detection data (n = 20,262; 20.3%). Of those, 43.3% also include count data (n = 43,151). The information available in NEOTROPICAL CARNIVORES will contribute to macroecological, ecological, and conservation questions in multiple spatio‐temporal perspectives. As carnivores play key roles in trophic interactions, a better understanding of their distribution and habitat requirements are essential to establish conservation management plans and safeguard the future ecological health of Neotropical ecosystems. Our data paper, combined with other large‐scale data sets, has great potential to clarify species distribution and related ecological processes within the Neotropics. There are no copyright restrictions and no restriction for using data from this data paper, as long as the data paper is cited as the source of the information used. We also request that users inform us of how they intend to use the data.

NEOTROPICAL ALIEN MAMMALS: a data set of occurrence and abundance of alien mammals in the Neotropics - Clarissa Alves da Rosa; Bruno R. Ribeiro; Vanesa Bejarano; Fernando Henrique Puertas; Adriana Bocchiglieri; Adriana Loeser dos Santos Barbosa; Adriano Garcia Chiarello; Adriano Pereira Paglia; Adriele Aparecida Pereira; Adryelle Francisca de Souza Moreira; Agnis Cristiane de Souza; Aiesca Pellegrin; et al. (Ecology, 2020)
Biological invasion is one of the main threats to native biodiversity. For a species to become invasive, it must be voluntarily or involuntarily introduced by humans into a nonnative habitat. Mammals were among first taxa to be introduced worldwide for game, meat, and labor, yet the number of species introduced in the Neotropics remains unknown. In this data set, we make available occurrence and abundance data on mammal species that (1) transposed a geographical barrier and (2) were voluntarily or involuntarily introduced by humans into the Neotropics. Our data set is composed of 73,738 historical and current georeferenced records on alien mammal species of which around 96% correspond to occurrence data on 77 species belonging to eight orders and 26 families. Data cover 26 continental countries in the Neotropics, ranging from Mexico and its frontier regions (southern Florida and coastal‐central Florida in the southeast United States) to Argentina, Paraguay, Chile, and Uruguay, and the 13 countries of Caribbean islands. Our data set also includes neotropical species (e.g., Callithrix sp., Myocastor coypus , Nasua nasua) considered alien in particular areas of Neotropics. The most numerous species in terms of records are from Bos sp. ( n = 37,782), Sus scrofa ( n = 6,730), and Canis familiaris ( n = 10,084); 17 species were represented by only one record (e.g., S yncerus caffer, Cervus timorensis, Cervus unicolor, Canis latrans ). Primates have the highest number of species in the data set ( n = 20 species), partly because of uncertainties regarding taxonomic identification of the genera Callithrix, which includes the species Callithrix aurita, Callithrix flaviceps, Callithrix geoffroyi, Callithrix jacchus, Callithrix kuhlii, Callithrix penicillata , and their hybrids. This unique data set will be a valuable source of information on invasion risk assessments, biodiversity redistribution and conservation‐related research. There are no copyright restrictions. Please cite this data paper when using the data in publications. We also request that researchers and teachers inform us on how they are using the data.

Interaction of phytohormone-producing rhizobia with sugarcane mini-setts and their effect on plant development - Natália S. Ferreira; Gustavo F. Matos; Carlos H. S. G. Meneses; Veronica M. Reis; Janaina R. C. Rouws; Stefan Schwab; José I. Baldani; Luc F. M. Rouws (Plant and Soil, 2020)

Pilot-Scaled Fast-Pyrolysis Conversion of Eucalyptus Wood Fines into Products: Discussion Toward Possible Applications in Biofuels, Materials, and Precursors - Mailson Matos; Bruno D. Mattos; Pedro H. G. de Cademartori; Tainise V. Lourençon; Fabrício A. Hansel; Patrícia R. S. Zanoni; Carlos I. Yamamoto; Washington L. E. Magalhães (BioEnergy Research, 2020)

Commercial Red Seaweed in Portugal (Gelidium sesquipedale and Pterocladiella capillacea, Florideophyceae): Going beyond a Single-Purpose Product Approach by Valorizing Bioactivity - J. Matos; A. Gomes; C. Cardoso; C. Afonso; A. M. Campos; R. Gomes; P. Falé; Inês Delgado; Inês Coelho; Isabel Castanheira; N. M. Bandarra (Thalassas: An International Journal of Marine Sciences, 2020)

Adenosine and NMDA Receptors Modulate Neuroprotection-Induced NMDA Preconditioning in Mice - Adriana B. Ghislandi; Michelle L. Garcez; Gabriela M. Zambon; Leandra C. Constantino; Douglas N. Matos; Bruna B. Pescador; Carla I. Tasca; Carina R. Boeck (Journal of Molecular Neuroscience, 2020)

Modulation of P2Y2 receptors in bovine cumulus oocyte complexes: effects on intracellular calcium, zona hardening and developmental competence - E. Fonseca; P. Mesquita; C. C. Marques; M. C. Baptista; J. Pimenta; J. E. Matos; G. Soveral; R. M. L. N. Pereira (Purinergic Signalling, 2020)

Do Workers from Subspecies Acromyrmex subterraneus Prepare Leaves and Toxic Baits in Similar Ways for Their Fungus Garden? - L. C. Forti; A. P. P. Andrade; K. K. A. Sousa; R. S. Camargo; C. A. O. Matos; N. Caldato; G. C. Catalani; V. M. Ramos (Neotropical Entomology, 2020)

Secondary forest fragments offer important carbon and biodiversity cobenefits - Fabio A. R. Matos; Luiz F. S. Magnago; Carlos Aquila Chan Miranda; Luis F. T. de Menezes; Markus Gastauer; Nathália V. H. Safar; Carlos E. G. R. Schaefer; Mônica P. da Silva; Marcelo Simonelli; Felicity A. Edwards; Sebastião V. Martins; João A. A. Meira‐Neto; et al. (Global Change Biology, 2020)
Tropical forests store large amounts of carbon and high biodiversity, but are being degraded at alarming rates. The emerging global Forest and Landscape Restoration (FLR) agenda seeks to limit global climate change by removing carbon dioxide from the atmosphere through the growth of trees. In doing so, it may also protect biodiversity as a free cobenefit, which is vital given the massive shortfall in funding for biodiversity conservation. We investigated whether natural forest regeneration on abandoned pastureland offers such cobenefits, focusing for the first time on the recovery of taxonomic diversity (TD), phylogenetic diversity (PD) and functional diversity (FD) of trees, including the recovery of threatened and endemic species richness, within isolated secondary forest (SF) fragments. We focused on the globally threatened Brazilian Atlantic Forest, where commitments have been made to restore 1 million hectares under FLR. Three decades after land abandonment, regenerating forests had recovered ~20% (72 Mg/ha) of the above‐ground carbon stocks of a primary forest (PF), with cattle pasture containing just 3% of stocks relative to PFs. Over this period, SF recovered ~76% of TD, 84% of PD and 96% of FD found within PFs. In addition, SFs had on average recovered 65% of threatened and ~30% of endemic species richness of primary Atlantic forest. Finally, we find positive relationships between carbon stock and tree diversity recovery. Our results emphasize that SF fragments offer cobenefits under FLR and other carbon‐based payments for ecosystem service schemes (e.g. carbon enhancements under REDD+). They also indicate that even isolated patches of SF could help to mitigate climate change and the biodiversity extinction crisis by recovering species of high conservation concern and improving landscape connectivity.

Can Acacia mangium and Acacia auriculiformis hinder restoration efforts in the Brazilian Atlantic Forest under current and future climate conditions? - Gustavo Heringer; Marcelo L. Bueno; João A. A. Meira-Neto; Fábio A. R. Matos; Andreza V. Neri (Biological Invasions, 2019)

NEOTROPICAL XENARTHRANS: a data set of occurrence of xenarthran species in the Neotropics - Paloma Marques Santos; Adriana Bocchiglieri; Adriano Garcia Chiarello; Adriano Pereira Paglia; Adryelle Moreira; Agnis Cristiane de Souza; Agustin Manuel Abba; Agustin Paviolo; Ailin Gatica; Akyllan Zoppi Medeiro; Alan Nilo Costa; Alberto Gonzalez Gallina; et al. (Ecology, 2019)
Xenarthrans—anteaters, sloths, and armadillos—have essential functions for ecosystem maintenance, such as insect control and nutrient cycling, playing key roles as ecosystem engineers. Because of habitat loss and fragmentation, hunting pressure, and conflicts with domestic dogs, these species have been threatened locally, regionally, or even across their full distribution ranges. The Neotropics harbor 21 species of armadillos, 10 anteaters, and 6 sloths. Our data set includes the families Chlamyphoridae (13), Dasypodidae (7), Myrmecophagidae (3), Bradypodidae (4), and Megalonychidae (2). We have no occurrence data on Dasypus pilosus (Dasypodidae). Regarding Cyclopedidae, until recently, only one species was recognized, but new genetic studies have revealed that the group is represented by seven species. In this data paper, we compiled a total of 42,528 records of 31 species, represented by occurrence and quantitative data, totaling 24,847 unique georeferenced records. The geographic range is from the southern United States, Mexico, and Caribbean countries at the northern portion of the Neotropics, to the austral distribution in Argentina, Paraguay, Chile, and Uruguay. Regarding anteaters, Myrmecophaga tridactyla has the most records ( n = 5,941), and Cyclopes sp. have the fewest ( n = 240). The armadillo species with the most data is Dasypus novemcinctus ( n = 11,588), and the fewest data are recorded for Calyptophractus retusus ( n = 33). With regard to sloth species, Bradypus variegatus has the most records ( n = 962), and Bradypus pygmaeus has the fewest ( n = 12). Our main objective with Neotropical Xenarthrans is to make occurrence and quantitative data available to facilitate more ecological research, particularly if we integrate the xenarthran data with other data sets of Neotropical Series that will become available very soon (i.e., Neotropical Carnivores, Neotropical Invasive Mammals, and Neotropical Hunters and Dogs). Therefore, studies on trophic cascades, hunting pressure, habitat loss, fragmentation effects, species invasion, and climate change effects will be possible with the Neotropical Xenarthrans data set. Please cite this data paper when using its data in publications. We also request that researchers and teachers inform us of how they are using these data.

Effect of temperature on the thermal conductivity of a granite with high heat production from Central Portugal - M. M. Miranda; C. R. Matos; N. V. Rodrigues; A. J. S. C. Pereira; J. J. Costa (Journal of Iberian Geology, 2019)

Efficient biotechnological synthesis of flavor esters using a low-cost biocatalyst with immobilized Rhizomucor miehei lipase - Ulisses M. F. de Oliveira; Leonardo J. B. Lima de Matos; Maria Cristiane M. de Souza; Bruna B. Pinheiro; José C. S. dos Santos; Luciana R. B. Gonçalves (Molecular Biology Reports, 2019)

Spider mites escape bacterial infection by avoiding contaminated food - Flore Zélé; Gonçalo Santos-Matos; Alexandre R. T. Figueiredo; Cátia Eira; Catarina Pinto; Telma G. Laurentino; Élio Sucena; Sara Magalhães (Oecologia, 2019)

Electron paramagnetic resonance (EPR) spectroscopy as a tool for the characterization of biochar from guava waste - Tassya T. S. Matos; Antônio S. Mangrich; Estela M. C. Cardoso; Juliana Schultz; Mayara R. Fornari; Alberto Wisniewski; Ingrid S. C. Carregosa (Journal of Soils and Sediments, 2019)

Foraging strategies of a generalist seabird species, the yellow-legged gull, from GPS tracking and stable isotope analyses - Roberto F. Mendes; Jaime A. Ramos; Vitor H. Paiva; Joana G. Calado; Diana M. Matos; Filipe R. Ceia (Marine Biology, 2018)

Pre-hatching development in the intertidal zone negatively affects juvenile survival and physiology in the muricid gastropod Acanthina monodon - O. R. Chaparro; L. P. Salas-Yanquin; A. S. Matos; J. A. Bűchner-Miranda; M. W. Gray; V. M. Cubillos; J. A. Pechenik (Marine Biology, 2018)

Creation of a coastal evolution prognostic model using shoreline historical data and techniques of digital image processing in a GIS environment for generating future scenarios - Willamys R. N. de Sousa; Michael V. S. Souto; Stefanny S. Matos; Cynthia R. Duarte; Ana R. G. N. L. Salgueiro; Cláudio A. da Silva Neto (International Journal of Remote Sensing, 2018)

Climate Change Impacts on Seagrass Meadows and Macroalgal Forests: An Integrative Perspective on Acclimation and Adaptation Potential - Bernardo Duarte; Irene Martins; Rui Rosa; Ana R. Matos; Michael Y. Roleda; Thorsten B. H. Reusch; Aschwin H. Engelen; Ester A. Serrão; Gareth A. Pearson; João C. Marques; Isabel Caçador; Carlos M. Duarte; et al. (Frontiers in Marine Science, 2018)

Importance of tissue sampling, laboratory methods, and patient characteristics for detection of Pneumocystis in autopsied lungs of non-immunosuppressed individuals - S. L. Vargas; C. Ponce; R. Bustamante; E. Calderón; G. Nevez; Y. De Armas; O. Matos; R. F. Miller; M. J. Gallo (European Journal of Clinical Microbiology & Infectious Diseases, 2017)

In Silico, In Vitro and In Vivo Toxicological Assessment of BPP-BrachyNH2, A Vasoactive Proline-Rich Oligopeptide from Brachycephalus ephippium - Daniel D. R. Arcanjo; Ana Carolina Mafud; Andreanne G. Vasconcelos; José Couras da Silva-Filho; Maurício P. M. Amaral; Lucas M. Brito; Marcelo P. Bemquerer; Selma A. S. Kückelhaus; Alexandra Plácido; Cristina Delerue-Matos; Nuno Vale; Yvonne P. Mascarenhas; et al. (International Journal of Peptide Research and Therapeutics, 2017)

System Development for Concomitant Degradation of Pesticides and Power Generation - Andréia Peiter; Tanna E. R. Fiuza; Roberto de Matos; Augusto Celso Antunes; Sandra Regina Masetto Antunes; Cleber A. Lindino (Water, Air, & Soil Pollution, 2017)

Variation in stem mortality rates determines patterns of above‐ground biomass in A mazonian forests: implications for dynamic global vegetation models - Michelle O. Johnson; David Galbraith; Manuel Gloor; Hannes De Deurwaerder; Matthieu Guimberteau; Anja Rammig; Kirsten Thonicke; Hans Verbeeck; Celso von Randow; Abel Monteagudo; Oliver L. Phillips; Roel J. W. Brienen; et al. (Global Change Biology, 2016)
Understanding the processes that determine above‐ground biomass ( AGB ) in Amazonian forests is important for predicting the sensitivity of these ecosystems to environmental change and for designing and evaluating dynamic global vegetation models ( DGVM s). AGB is determined by inputs from woody productivity [woody net primary productivity ( NPP )] and the rate at which carbon is lost through tree mortality. Here, we test whether two direct metrics of tree mortality (the absolute rate of woody biomass loss and the rate of stem mortality) and/or woody NPP , control variation in AGB among 167 plots in intact forest across Amazonia. We then compare these relationships and the observed variation in AGB and woody NPP with the predictions of four DGVM s. The observations show that stem mortality rates, rather than absolute rates of woody biomass loss, are the most important predictor of AGB , which is consistent with the importance of stand size structure for determining spatial variation in AGB . The relationship between stem mortality rates and AGB varies among different regions of Amazonia, indicating that variation in wood density and height/diameter relationships also influences AGB . In contrast to previous findings, we find that woody NPP is not correlated with stem mortality rates and is weakly positively correlated with AGB . Across the four models, basin‐wide average AGB is similar to the mean of the observations. However, the models consistently overestimate woody NPP and poorly represent the spatial patterns of both AGB and woody NPP estimated using plot data. In marked contrast to the observations, DGVM s typically show strong positive relationships between woody NPP and AGB . Resolving these differences will require incorporating forest size structure, mechanistic models of stem mortality and variation in functional composition in DGVM s.

Mucoadhesive nanoparticles: a new perspective for fish drug application - A C da S Costa; H M Brandão; S R da Silva; A R Bentes‐Sousa; J A P Diniz; J de J Viana Pinheiro; M de F C de Melo; J O C Silva; E R Matos; R M Ribeiro‐Costa (Journal of Fish Diseases, 2016)

Oral and endotracheal tubes colonization by periodontal bacteria: a case–control ICU study - A. N. Porto; S. C. Cortelli; A. H. Borges; F. Z. Matos; D. R. Aquino; T. B. Miranda; F. Oliveira Costa; A. F. Aranha; J. R. Cortelli (European Journal of Clinical Microbiology & Infectious Diseases, 2016)

Porphyrin interaction with the membrane: the use of membrane models to elicit the diverse partition in normal and neoplastic tissue - Carla Matos; Cláudia Ribeiro; Lígia R. Gomes (Medicinal Chemistry Research, 2015)

(1–3)-Beta-D-glucan in association with lactate dehydrogenase as biomarkers of Pneumocystis pneumonia (PcP) in HIV-infected patients - F. Esteves; C.-H. Lee; B. de Sousa; R. Badura; M. Seringa; C. Fernandes; J. F. Gaspar; F. Antunes; O. Matos (European Journal of Clinical Microbiology & Infectious Diseases, 2014)

Chemical composition of the essential oil of Lippia gracilis Schauer leaves and its potential as modulator of bacterial resistance - Vanessa de Carvalho Nilo Bitu; Heberty Di Tarso Fernandes Fecundo; José Galberto Martins da Costa; Henrique Douglas Melo Coutinho; Fabíola Fernandes G. Rodrigues; Nathalia Matos de Santana; Marco Antônio Botelho; Irwin R. Alencar Menezes (Natural Product Research, 2014)

Tadalafil-induced improvement in left ventricular diastolic function in resistant hypertension - Rodrigo C. Santos; Ana Paula C. de Faria; Natália R. Barbaro; Rodrigo Modolo; Silvia E. Ferreira-Melo; José R. Matos-Souza; Otávio R. Coelho; Juan C. Yugar-Toledo; Vanessa Fontana; David Calhoun; Heitor Moreno (European Journal of Clinical Pharmacology, 2014)

Geology of the Rosário–Neves Corvo antiform, Iberian Pyrite Belt, Portugal: new insights from physical volcanology, palynostratigraphy and isotope geochronology studies - J. T. Oliveira; C. J. P. Rosa; Z. Pereira; D. R. N. Rosa; J. X. Matos; C. M. C. Inverno; T. Andersen (Mineralium Deposita, 2013)

Fast evolutionary genetic differentiation during experimental colonizations - JOSIANE SANTOS; MARTA PASCUAL; PEDRO SIMÕES; INÊS FRAGATA; MICHAEL R. ROSE; MARGARIDA MATOS (Journal of Genetics, 2013)

Does the magnocellular octaval nucleus process auditory information in the toadfish, Opsanus tau? - Peggy L. Edds-Walton; Solymar Rivera Matos; Richard R. Fay (Journal of Comparative Physiology A, 2013)

Interleukin-6 gene −174G>C and −636G>C promoter polymorphisms and prostate cancer risk - J. F. Magalhães; A. J. Cortinhas; C. M. Albuquerque; C. S. Baptista; R. Ribeiro; Carlos Viegas; Augusto Matos; João Machado; Maria A. Pires; Henrique Guedes-Pinto; A. Martins-Bessa; J. C. Leitão; et al. (Molecular Biology Reports, 2013)

Alcohol and tobacco, and the risk of cancers of the upper aerodigestive tract in Latin America: a case–control study - K. Szymańska; R. J. Hung; V. Wünsch-Filho; J. Eluf-Neto; M. P. Curado; S. Koifman; E. Matos; A. Menezes; L. Fernandez; A. W. Daudt; P. Boffetta; P. Brennan (Cancer Causes & Control, 2011)

Steady-state level of epidermal growth factor (EGF) mRNA and effect of EGF on in vitro culture of caprine preantral follicles - Juliana Jales H. Celestino; Jamily B. Bruno; Márcia Viviane A. Saraiva; Rebeca M. P. Rocha; Ivina R. Brito; Ana Beatriz G. Duarte; Valdevane R. Araújo; Cleidson M. G. Silva; Maria Helena T. Matos; Claudio C. Campello; José Roberto V. Silva; José Ricardo Figueiredo (Cell and Tissue Research, 2011)

Using zeta-potential measurements to quantify peptide partition to lipid membranes - João M. Freire; Marco M. Domingues; Joana Matos; Manuel N. Melo; Ana Salomé Veiga; Nuno C. Santos; Miguel A. R. B. Castanho (European Biophysics Journal, 2011)

Molecular insight into the population structure of common and spotted dolphins inhabiting the pelagic waters of the Northeast Atlantic - Sophie Quérouil; Luís Freitas; Irma Cascão; Filipe Alves; Ana Dinis; Joana R. Almeida; Rui Prieto; Silvia Borràs; José A. Matos; Diogo Mendonça; Ricardo S. Santos (Marine Biology, 2010)

Drinking of maté and the risk of cancers of the upper aerodigestive tract in Latin America: a case–control study - K. Szymańska; E. Matos; R. J. Hung; V. Wünsch-Filho; J. Eluf-Neto; A. Menezes; A. W. Daudt; P. Brennan; P. Boffetta (Cancer Causes & Control, 2010)

A new species of Thelypteris (Thelypteridaceae) from southern Bahia, Brazil - Fernando B. Matos; Alan R. Smith; Paulo H. Labiak (Brittonia, 2010)

An anti-inflammatory lectin from Luetzelburgia auriculata seeds inhibits adhesion and rolling of leukocytes and modulates histamine and PGE2 action in acute inflammation models - N. M. N. Alencar; R. S. B. Oliveira; J. G. Figueiredo; I. J. M. Cavalcante; M. P. V. Matos; F. Q. Cunha; J. V. S. Nunes; L. R. Bomfim; M. V. Ramos (Inflammation Research, 2010)

Assessment of high-level gentamicin and glycopeptide-resistant Enterococcus faecalis and E. faecium clonal structure in a Portuguese hospital over a 3-year period - R. Mato; F. Almeida; R. Pires; P. Rodrigues; T. Ferreira; I. Santos-Sanches (European Journal of Clinical Microbiology & Infectious Diseases, 2009)

Bulk adhesive strength of recombinant hybrid mussel adhesive protein - Hyung Joon Cha; Dong Soo Hwang; Seonghye Lim; James D. White; Cristina R. Matos-Perez; Jonathan J. Wilker (Biofouling, 2009)

Bacteria Associated with Toxic Clonal Cultures of the Dinoflagellate Ostreopsis lenticularis - Lumarie Pérez-Guzmán; Ana E. Pérez-Matos; William Rosado; Thomas R. Tosteson; Nadathur S. Govind (Marine Biotechnology, 2008)

Environmental assessment of water-courses of the Turvo Limpo River basin at the Minas Gerais State, Brazil - C. P. Jordão; P. R. S. Ribeiro; A. T. Matos; R. K. X. Bastos; R. B. A. Fernandes; R. L. F. Fontes (Environmental Monitoring and Assessment, 2007)

Effects of Cu, Ni and Zn on Lettuce Grown in Metal-Enriched Vermicompost Amended Soil - C. P. Jordão; L. L. Fialho; P. R. Cecon; A. T. Matos; J. C. L. Neves; E. S. Mendonça; R. L. F. Fontes (Water, Air, & Soil Pollution, 2006)

Cholesterol depletion by methyl-?-cyclodextrin enhances myoblast fusion and induces the formation of myotubes with disorganized nuclei - Cludia S. Mermelstein; Dbora M. Portilho; Rommel B. Medeiros; Aline R. Matos; Marcelo Einicker-Lamas; Giovane G. Tortelote; Adalberto Vieyra; Manoel L. Costa (Cell and Tissue Research, 2005)

Quantitative genetics of functional characters inDrosophila melanogaster populations subjected to laboratory selection - Henrique Teotónio; Margarida Matos; Michael R. Rose (Journal of Genetics, 2004)

Assessment of Water Systems for Contaminants from Domestic and Industrial Sewages - C. P. Jordão; M. G. Pereira; C. R. Bellato; J. L. Pereira; A. T. Matos (Environmental Monitoring and Assessment, 2002)

Fire and restoration of the largest urban forest of the world in Rio de Janeiro City, Brazil - D.M. Silva Matos; C. Junius F. Santos; D. de R. Chevalier (Urban Ecosystems, 2002)

First record of emergency queen rearing in stingless bees (Hymenoptera, Apinae, Meliponini) - C.D. Faustino; E.V. Silva-Matos; S. Mateus; R. Zucchi (Insectes Sociaux, 2002)

Effects of pH and Dose on Nasal Absorption of Scopolamine Hydrobromide in Human Subjects - Shamim Ahmed; Anthony P. Sileno; Jorge C. deMeireles; Ramneik Dua; Harish K. Pimplaskar; Wei J. Xia; John Marinaro; Edward Langenback; Frank J. Matos; Lakshmi Putcha; Vincent D. Romeo; Charan R. Behl (Pharmaceutical Research, 2000)